2021
DOI: 10.1016/j.gore.2021.100817
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in multiresistant metastatic choriocarcinoma after pembrolizumab treatment: A case report

Abstract: Highlights Checkpoint inhibitor therapy affecting PD-L1 as treatment for advanced solid tumors. Success in trial pembrolizumab therapy in multiresistant metastatic choriocarcinoma. Long-term remission after pembrolizumab therapy in multiresistant choriocarcinoma. Only six reported cases, one with comparable follow-up and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Immunohistochemical analysis showed the expression of PD-L1 in 90% of tumor cells and in 5% of immune cells. Based on these findings, she was treated with seven cycles of Pembrolizumab, achieving complete disease remission twenty-four months after the end of treatment [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical analysis showed the expression of PD-L1 in 90% of tumor cells and in 5% of immune cells. Based on these findings, she was treated with seven cycles of Pembrolizumab, achieving complete disease remission twenty-four months after the end of treatment [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, experts from Charing Cross Hospital in the United Kingdom reported for the first time that drug-resistant CC patients who received pembrolizumab achieved a complete response. 31 Next, Huang et al 29 and Paspalj et al 32 showed the dramatic efficacy of pembrolizumab in cases with recurrent CC. Despite the favorable outcome and safety of ICIs for CC, they are currently implemented only in salvage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple case reports supporting the efficacy and low toxicity of pembrolizumab in gestational trophoblastic neoplasia have subsequently been published. [23][24][25][26][27] Across these reports, 12 out of 17 patients with multidrug-resistant disease went on to have human chorionic gonadotropin normalization. The majority had PD-L1 expression of >90% and treatment was well tolerated throughout.…”
Section: Checkpoint Immunotherapy Has Revolutionized Cancer Carementioning
confidence: 99%